Efek potensiasi kombinasi sefadroksil dan ekstrak camellia sinensis terhadap pertumbuhan aggregatibacter actinomycetemcomitans Dan porphyromonas gingivalis - Karyn Priscila; Didi Nugroho Santosa (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Cefadroxil, betalactam antibiotic belonging to cephalosporin class, is a drug of choice for treating periodontal infection. Previous studies reported that addition of green tea (Camellia sinensis) extract to betalactam antibiotics has shown synergistic antibacterial effect. Objective: To examine the antibacterial effect of GTE combined with cefadroxil on A. actinomycetemcomitans and P. gingivalis growth. Methods: In vitro experimental with post-test-only control design, conducted at MiCORE Laboratory, Trisakti University Faculty of Dentistry. There were 8 treatments: combination of cefadroxil 8 µg/mL with GTE 3,125 mg/mL, 6,25 mg/mL, and 12,5 mg/mL, GTE 3,125 mg/mL, 6,25 mg/mL, and 12,5 mg/mL, cefadroxil 16 µg/mL, and NaOH 0,1 N. Results: In treatment of solely GTE and NaOH 0,1, no inhibition zones were found. Meanwhile, combination of cefadroxil 8 µg/mL with GTE 3,125 mg/mL, 6,25 mg/mL, and 12,5 mg/mL, and cefadroxil 16 µg/mL inhibited both bacteria’s growth. Treatment of cefadroxil 8 µg/mL combined with GTE 3,125 mg/mL resulted in the largest inhibition zone. One-way ANOVA test showed significant difference, then post hoc test showed that combination of cefadroxil 8 µg/mL with GTE 3,125 mg/mL and 6,25 mg/mL were not significantly different from the positive control. Conclusion: Potentiation effect occurred on combination of cefadroxil 8 µg/mL with GTE 3,125 mg/mL and 6,25 mg/mL against A. actinomycetemcomitans and P. gingivalis growth. Green tea extract could increase cefadroxil antibacterial effect up to twice larger.